Undervaluing Gratitude: Expressers Misunderstand the Consequences of Showing Appreciation. (September 2018) - Kumar, Amit; Epley, Nicholas
Expressing gratitude improves well-being for both expressers and recipients, but we suggest that an egocentric bias may lead expressers to systematically undervalue its positive impact on recipients in a way that could keep people from expressing gratitude more often in everyday life. Participants in three experiments wrote gratitude letters and then predicted how surprised, happy, and awkward recipients would feel. Recipients then reported how receiving an expression of gratitude actually made them feel. Expressers significantly underestimated how surprised recipients would be about why expressers were grateful, overestimated how awkward recipients would feel, and underestimated how positive recipients would feel. Expected awkwardness and mood were both correlated with participants' willingness to express gratitude. Wise decisions are guided by an accurate assessment of the expected value of action. Underestimating the value of prosocial actions, such as expressing gratitude, may keep people from engaging in behavior that would maximize their own—and others'—well-being.